Factors Associated With Coronary Artery Disease Progression Assessed By Serial Coronary Computed Tomography Angiography - Camargo,Gabriel Cordeiro (2017)
Abstract Background: Coronary computed tomography angiography (CCTA) allows for noninvasive coronary artery disease (CAD) phenotyping. Factors related to CAD progression are epidemiologically valuable. Objective: To identify factors associated with CAD progression in patients undergoing sequential CCTA testing. Methods: We retrospectively analyzed 384 consecutive patients who had at least two CCTA studies between December 2005 and March 2013. Due to limitations in the quantification of CAD progression, we excluded patients who had undergone surgical revascularization previously or percutaneous coronary intervention (PCI) between studies. CAD progression was defined as any increase in the adapted segment stenosis score (calculated using the number of diseased segments and stenosis severity) in all coronary segments without stent (in-stent restenosis was excluded from the analysis). Stepwise logistic regression was used to assess variables associated with CAD progression. Results: From a final population of 234 patients, a total of 117 (50%) had CAD progression. In a model accounting for major CAD risk factors and other baseline characteristics, only age (odds ratio [OR] 1.04, 95% confidence interval [95%CI] 1.01-1.07), interstudy interval (OR 1.03, 95%CI 1.01-1.04), and past PCI (OR 3.66, 95%CI 1.77-7.55) showed an independent relationship with CAD progression. Conclusions: A history of PCI with stent placement was independently associated with a 3.7-fold increase in the odds of CAD progression, excluding in-stent restenosis. Age and interstudy interval were also independent predictors of progression.